Development of E-Comic Based Learning Media on Large and Unit Materials to Increase Student Learning Motivation - Eliza Septiana (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2022)
This study aims to determine the perception and feasibility of e-comics that will be developed to increase the learning motivation of high school students. This research is a follow-up research that has been carried out previously which is only up to the analysis stage. The research method carried out is R n D with the ADDIE model which has five stages, namely; analysis stage (analysis); design ; development ; implementation (use); evaluation, but this research is only carried out until the development stage. The assessment instrument used in this study is an expert validation sheet consisting of several aspects, namely; material aspects, language aspects, and media aspects. Based on the results of the product validation test from the validator, a percentage of the score was obtained 92.5% for the material aspect, 90% for the language aspect, 82.4% for the media aspect, and 77.08% for the motivation aspect so that the total average score is 90% which is included in the very decent category. The results of the student perception response showed a good response with a percentage of 78.94%. Thus E-Comics material of Magnitude and Units to Increase Motivation of High School Students becomes a product worthy of use